Pengaruh Motivasi, Komunikasi, dan Kompetensi terhadap Kinerja Guruyy SDIT Muhammadiyah Al-Kautsar: Studi Kasus pada SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura - Safi’i, Muhammad; Maryam, Siti; Suryo, Ibnu (EduInovasi: Journal of Basic Educational Studies, 2024)
To analyze the efffect motivation, communication, and competency on teacher performanca an the Muhammadiyah Al-Kautsar Elementary school, this researchis is a descriptiv qualitative study with primary data types. the population is 61 people, for that the sample take from the population must be truly representative, totaling 51 people. Methods off data collection’s using questionaire interview’s, and documentation’s questionnaire data, tested with multiplle liniar regression analysis. Motivation has a substantial beneficial influence, as does communication, and competence has a fairly positive effect on teacher performances at SD Muhammadiyah Al-Kautsar. The findings of the coefficient in determimination obtained 85,8% from performance can be explained by the independent variablee of motivation, communicatoion and competencee. it is hoped that the school can place or give assignments to teachers according to the competencies they have, so that they can improve the teacher's ability to complete work better. Furthermore, skill affects instructor execution, work environment, and salary that might effect how well teachers perform, you can develop your research utilizing other independent variables.